Who dreams this dreaming? Patanjali's symbolic usurpation of the trope of the 'enslaved' Indian economy. Issue 6 (2nd November 2018) - Siganporia, Harmony
ABSTRACT: Scholars have argued that the national economy is the symbolic rallying point around which the idea of India has long been grafted, from its depiction as 'enslaved' in colonial times to being enshrined at the heart of the nation-building processes which marked the early years of post-independence India. The past decade has seen the meteoric rise of a local fast-moving consumer goods giant which is the brainchild of an ascetic named Baba Ramdev. This company, Patanjali, is today valued at just over Rs. 10, 000 crores (US$1560 million), and is India's second largest consumer goods company. To be read in the narrative crafted around Patanjali is a return to the notion of the enslaved Indian economy, with new villains here cast – foreign multinational players standing in for the English within the colonial framework – from whom India (starting conveniently with its economy) must be saved. This new 'swadeshi' (home-grown or locally made) movement seeks to create, in its own words, 'patriots' out of consumers, forging a new national culture on the anvil of an overtly capitalist base. This article critically analyses Patanjali's communication, and seeks to revisit the question of the role played by the national economy in this iteration of India's dreaming.